Sea-land climate gradient: a factor influencing vegetation phenology patterns in Yellow River Delta region - Ruyun Liu; Quanzhou Yu; Yujie Liu; Junjie Chen; Tianquan Liang; Qingxin Tang; Yongjin Chen; Jicai Ning; Zhenguo Niu; Shaoqiang Wang (Environmental Research Communications)
Estuarine coastal wetland are vulnerable zones of the Earth’s ecosphere, and hygrophilous vegetation responds sensitively to climate change. Vegetation phenology is a key component of global climate change research. However, due to the diversity of vegetation types and the influence of sea-land interaction, the characteristics of phenology in coastal wetlands are poorly understood. Therefore, we took the vegetation in the Yellow River Delta (YRD) wetland in China as a research object. The Gap Filling and Savitzky–Golay algorithm was selected to fuse MODIS_NDVI with Landsat for extracting vegetation phenology based on classification. Then we revealed their spatial-temporal variation and influencing mechanisms. Results showed YRD was rich in vegetation species. In addition to agricultural vegetation, the constructive species included Spartina alterniflora, Tamarix chinensis, Phragmites australis and Suaeda glauca. Vegetation phenology parameters, including Start of the growing season (SOS), End of the growing season (EOS) and Length of the growing season (LOS), showed various patterns in different years. The SOS showed a fluctuating advance trend, with the rate of 1.7 day per year (R ^2 = 0.58, p = 0.032). The EOS was relatively stable, the LOS showed a decreasing and then fluctuating upward trend, with the extended rate of 4.4 day per year. Spatially, SOS and EOS showed a trend of advancement from the northeast to the southwest. The changes in phenology were mainly influenced by spring precipitation and last autumn temperature. Meanwhile, there was a significant seaward phenology pattern of vegetation. The Spartina alterniflora, Phragmites australis, and Tamarix chinensis of SOS and EOS showed a trend of advancing the further they were from the sea. The phenology parameters were significantly different among buffer zones. The distance from the ocean will have an impact on the phenological time of vegetation. Differences in temperature and precipitation within each buffer zone had a significant effect on phenology.